First report of winter epizootic of salmon lice on sea trout in Norway - KW Vollset (Inter-Research, 2014)
Here we report on the first observation of a winter epizootic of salmon lice Lepeophtheirus salmonis Krøyer on sea trout Salmo trutta Linnaeus in a Norwegian fjord with intensive salmon farming. Trouts were sampled and counts of lice in the field were made for 2 consecutive winter seasons with trap nets in 2013 and 2014 just inside and outside the border to the National Salmon Fjord in Sognefjorden, western Norway. The aim of the study was to document potential epizootic outbreaks during the winter months. Following reports and field registrations of high abundance of lice in February and early March 2014, 12 and 14 fish were sampled from the 2 locations between 9 and 24 March and analyzed in the laboratory. Prevalence of sea lice on sampled fish inside and outside the fjord was 100 and 74%, with a mean abundance of 254.3 and 26.8 and a mean average intensity of 254.3 (max = 759) and 37.5 (max = 188), respectively. Chalimus stages dominated on the fish. In comparison, prevalence and abundance based on field observations in 2013 were low and dominated by adult stages. We suggest that the winter epizootic observed in 2014 and not in 2013 may be a result of the combined effect of production of salmon lice in nearby fish farms and the prevailing environmental conditions.